A Case Study – Role of Leech Therapy (Jalaukavcharana) in Varicose Vein. - Bhati, Dashrath Singh; Sharma, Vishnu Dutt; Gupta, Rajesh Kumar (International Research Journal of Ayurveda & Yoga, 2021)
Varicose veins are saccular dilatations of veins that are frequently convoluted. Certain vocations, such as bus drivers and police officers, necessitate lengthy standing, and those who work in these positions are prone to varicose veins. It can also happen to those who do a lot of muscle work, including rickshaw pullers and sportsmen. Varicose veins are often referred to Sirajagranthi in Ayurveda. According to Acharya Sushruta, Vata prakopaka nidanas such as physical exertion and straining cause Vata to enter the Siras, creating Sampeedana, Sankocha, and Vishoshana and triggering Granthi production in the Siras, displaying Sirajagranthi. Ayurveda reveals Raktamokshana as a treatment for varicose veins. Raktamokshanawas done as Jalaukavacharana. This is a case study of a 36-year-old male patient with a history of varicose veins who complained of discomfort, muscular spasms, and blackish discoloration over the past three years. Before 5 years ago, he had a varicose vein stripping operation for the same issue. Jalaukavacharana was performed once a week for one month. The patient had complete relief from all symptoms, as well as a noticeable improvement in the blackish discoloration of both legs.